Assessment of the risks of occupational injury and illness for the position of sanitar worker - George Mit; Claudiu Babiş; Elena Anda Botoc; Anișoara Habuc; Andrei Dimitescu (Journal of Research and Innovation for Sustainable Society)
This paper presents a risk assessment and action plan for the sanitation worker position using the INCDPM method. This method prioritizes risks based on their severity and allocates resources effectively for labor protection. For the sanitation worker position, 40 risk factors were identified. The overall risk level calculated is 3.40, categorizing it as a job with an acceptable risk level. The identified risk factors are broken down as follows: 35% are factors specific to the contractor, 10% are workload-related, 30% are related to the means of production, and 25% pertain to the work environment. This risk assessment enables a comprehensive view of occupational safety at each workplace, facilitating preventive measures according to Romanian and European Union health and safety legislation.